Representing Agrippina : constructions of female power in the early Roman Empire - Ginsburg, Judith (American classical studies, 2006)
Provides a fresh look at both the literary and material representations of Agrippina. This study exposes both the contrivances of the commissioned artists whose idealized portraits served to buttress the image of the regime and the contrasting designs of the historians whose rhetorical stereotypes and negative depictions aimed to undermine it.